Off-Target Effect of Sildenafil on Postsurgical Erectile Dysfunction: Alternate Pathways and Localized Delivery System. Issue 12 (1st December 2016) - Salmasi, Amirali; Lee, Geun Taek; Patel, Neal; Goyal, Ritu; Dinizo, Michael; Kwon, Young Suk; Modi, Part K.; Faiena, Izak; Kim, Hee-Jin; Lee, Nara; Hannan, Johanna L.; Kohn, Joachim; et al.
ABSTRACT: Introduction: There is no consensus on the best oral phosphodiesterase type 5 inhibitor (PDE5I) for patients undergoing penile rehabilitation after surgical nerve injury. Aim: To determine the mechanism of PDE5I on cultured neuronal cells and the effectiveness of local drug delivery using nanospheres (NSPs) to sites of nerve injury in a rat model of bilateral cavernous nerve injury (BCNI). Methods: The effects of sildenafil, tadalafil, and vardenafil on cyclic adenosine monophosphate, cyclic guanosine monophosphate, and cell survival after exposure to hypoxia and H2 O2 were measured in PC12, SH-SY5Y, and NTERA-2 (NT2) cell cultures. The effects of phosphodiesterase type 4 inhibitor (PDE4I) and PDE5I on neuronal cell survival were evaluated. Male rats underwent BCNI and were untreated (BCNI), immediately treated with application of empty NSPs (BCNI + NSP), NSPs containing sildenafil (Sild + NSP), or NSPs containing rolipram (Rol + NSP). Main Outcome Measures: Viability of neuronal cells was measured. Intracavernous pressure changes after cavernous nerve electrostimulation and expression of neurofilament, nitric oxide synthase, and actin in mid-shaft of penis were analyzed 14 days after injury. Results: Sildenafil and rolipram significantly decreased cell death after exposure to H2 O2 and hypoxia in PC12, SH-SY5Y, and NT2 cells. PC12 cells did not express PDE5 and knockdown of PDE4 significantly increased cell viability in PC12, SH-SY5Y, and NT2 cells exposed to hypoxia. The ratio of intracavernous pressure to mean arterial pressure and expression of penile neurofilament, nitric oxide synthase, and actin were significantly higher in the Sild + NSP and Rol + NSP groups than in the BCNI and BCNI + NSP groups. Limitations included analysis in only two PDE families using only a single dose. Conclusion: Sildenafil showed the most profound neuroprotective effect compared with tadalafil and vardenafil. Sildenafil- or rolipram-loaded NSP delivery to the site of nerve injury prevented erectile dysfunction and led to increased neurofilament, nitric oxide synthase, smooth muscle content in rat penile tissue after BCNI.